Design and implementation of a self-correcting non-retrodirective cross-eye jamming system using reference amplitude ratio and phase difference - Junghoon Lee; Byungkoo Park; Jinwoo Han; Jeil Jo (Scientific Reports)
Abstract This study presents a self-correction method for a non-retrodirective cross-eye jamming (NRCJ) system based on the measurement of reference amplitude ratio and phase difference (ARPD). Cross-eye jamming performance is highly sensitive to gain and phase mismatches between the system’s dual transmission paths, which can degrade the jamming effectiveness during operation. To address this issue, a reference system (RS) is introduced to measure the transmitted jamming signal in the jamming direction and compensate for deviations by adjusting the NRCJ system’s variable attenuator and phase shifter. The RS stores reference ARPD values during initial calibration and compares them with current measurements to update control parameters when errors exceed predefined thresholds. A prototype NRCJ system operating at 8 GHz was fabricated, and gain and phase errors of 2 dB and 3° were intentionally induced. Experimental results demonstrate that the proposed method successfully compensates for ARPD errors, reducing the gain and phase deviations to within 0.3 dB and 1°, respectively. Consequently, the magnitude of the cross-eye gain improved from 8.57 to 49.5, and the radar angle tracking error increased from 2.45° to 14.18°. These results confirm that the proposed self-correction approach enhances the robustness and jamming effectiveness of NRCJ systems in practical applications.